Russia's Past and Present in Animated Cartoons: a Sway Space Geography of Affect in Film-watching - Bennett, Sarah (My University, 2011)
Over the last decade, the urgency Russians have felt to distance themselves from their Soviet past has diminished, and cultural materials referencing that period have become popular. Film and animated film in Russia has followed the same trend, although analyses of Russian film have remained representational. This paper will use Russian animated films as a clearcut example to spur a theoretical innovation in non-representational theory. I will show how affect creates a virtual space among the viewer and the film, producing a geography that can push beyond the representational binaries of past and present. A variety of moments from Russian animated films will enrich this space, showing how it makes a Soviet culture possible in the present day.
Includes Appendices, Images, Bibliography and Filmography.
Keywords: Animated films; Cartoons; Russia